Impact of Pulmonary Risk Factors on Postoperative Outcomes Following Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis. (16th November 2020) - Elsamadicy, Aladine A; Freedman, Isaac G; Koo, Andrew B; David, Wyatt; Havlik, John; Reeves, Benjamin; Sarkozy, Margot; Kundishora, Adam; Sciubba, Daniel M; Kahle, Kristopher T; DiLuna, Michael
Abstract: INTRODUCTION: Pulmonary disease is a common comorbidity exacerbating surgical management of pediatric patients with adolescent idiopathic scoliosis (AIS). METHODS: A retrospective cohort study was performed using the National Surgical Quality Improvement Program-Pediatric database from 2016–2018. All pediatric patients with AIS undergoing PSF, or posterior arthrodesis for spinal deformity, were identified using the ICD-9-CM and ICD-10-CM coding system. Patients were categorized by whether they had recorded baseline Pulmonary Risk Factors (PRF) or no PRF. Patient demographics, comorbidities, intraoperative variables, complications, LOS, discharge disposition, and readmission rate were assessed. A multivariate stepwise logistic regression was used to determine the odds ratio for postoperative complication, extended LOS, and unplanned 30-day readmission. RESULTS: A total of 4, 929 patients were identified, of which 280 (5.7%) had baseline pulmonary risk factors. Age, sex, and racial makeup were similar between cohorts. The PRF cohort had a greater prevalence of comorbidities and lengthened operative times. The PRF cohort experienced bleed/transfusion sooner after surgery than the No-PRF cohort (PRF:2.0 ± 0.7 days vs. No-PRF:2.3 ± 4.7 days, P  = .02) and required greater total amount of blood transfused (PRF: 328.4±286.2 mL vs. No-PRF:294.4 ± 278.2 mL, P  = .03) yet overall rate of bleeding/transfusion was similar between cohorts ( P  = .83). Compared to the No-PRF cohort, the PRF cohort had higher rates of complications (PRF:4.3% vs. No-PRF:2.2%, P  = .03) and longer hospital stays (PRF:4.6 ± 4.3 days vs. No-PRF:3.8 ± 2.3 days, P  < .001) yet discharge disposition was similar between cohorts ( P  = .70). Rates of 30-day unplanned readmission were significantly higher in the PRF cohort (PRF:6.3% vs. No-PRF:2.7%, P  = .009) yet days to readmission ( P  = .76) and rates of 30-day reoperation ( P  = .16) were similar between cohorts. On multivariate analysis, PRF was a significant independent risk factor for longer hospital stays [RR:0.74, 95% CI:(0.44, 1.04), P  < .001] but not postoperative complication ( P  = .10) or 30-day unplanned readmission ( P  = .005) after Bonferroni correction. CONCLUSION: Our study demonstrated that pulmonary risk factors may be a risk factor for slightly longer hospital stays without higher rates of complication or unplanned readmissions for AIS patients undergoing PSF and thus should not preclude surgical management.